Analisis Tingkat Pengetahuan tentang Kanker Serviks pada SMA YAPIM Taruna Sei Glugur Rimbun Medan - Irfan Sazali Nasution; Azra Muzaiyana Nasution; Masry, Rifqa; Karolina, Josepin; Panggabean, Azuhra Widriyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Cancer remains one of the leading causes of death worldwide. Among the various types of cancer, cervical cancer is the fourth most common type of cancer in women globally and a significant cause of death. Cervical cancer is an abnormal cell growth in the cervix that can cause organ dysfunction. Human papilloma virus (HPV) infection is a major risk factor for cervical cancer, which is one of the leading causes of death in women worldwide. The aim of this study was to assess how well health education can increase adolescents' awareness and knowledge about cervical cancer. The research method used a cross-sectional design with three stages, namely pre-test, material delivery, and post-test. The sample consisted of 33 students of SMA YAPIM Taruna Sei Gelugur Rimbun Medan aged 15-17 years old. The results showed a significant increase in students' knowledge, from 56.19% during the pre-test to 78.67% when given the post-test. A total of 39.3% of respondents had good knowledge, 33.3% had fair knowledge, and 27.2% had poor knowledge. Health education was effective in improving adolescents' understanding of cervical cancer, including causes, prevention, and early detection. This study shows the important role of health education in schools in preventing infectious diseases, especially cervical cancer.